Childhood-Onset COPA Syndrome Recognized Retrospectively in the Context of Polyarticular Juvenile Idiopathic Arthritis and Rheumatoid Arthritis - Roko P. A. Nikolic; Cristina Moran Toro (Case Reports in Rheumatology, 2023)
COPA syndrome is a very rare autoinflammatory disorder manifesting with childhood-onset arthritis and pulmonary and renal disease, of which awareness may remain lacking. We present the case of a twenty-year-old male patient seen in the Young Adults with Rheumatic Disease clinic. Initially diagnosed with seropositive polyarticular juvenile idiopathic arthritis, the patient’s early childhood complaints of fatiguability, paroxysmal dyspnea, and pneumonia-like episodes were long to be felt unrelated to his arthritis. Upon transition to adult rheumatology care, a thorough review of the patient’s history prompted imaging which revealed interstitial lung disease. Restrictive spirometry and genetic testing confirmed the retrospective diagnosis of COPA syndrome.